(untitled) (Élisée - Revista de Geografia da UEG, 2023)
This text aims to analyze the demographic dynamics of small towns in the Center South and South Bahia between the years 1991 to 2010. For its development, a qualitative and quantitative methodology was used. In this way, a bibliographic survey was carried out related to the suggested theme and the space studied; data collection was also carried out on the municipalities in the study area in the IBGE Demographic Census of the years 1991, 2000 and 2010. Such data were tabulated with Microsoft Excel 2016 software, in addition, MapViewer 8 and QGis v3.16.6 software was usedmfor map making. Based on the information collected, demographic changes were observed in the municipalities, such as: urban growth, demographic decline in small towns and the rise of medium-sized cities. Thus, due to the fact that small cities make up a very varied universe in Brazil, empirical research is necessary to understand these realities.